PERAN PMDN DAN PMA TERHADAP PENURUNAN ANGKA KEMISKINAN DI INDONESIA - S, Suryatno Wiganepdo; Soegoto, Herman S (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
The purpose of this study is to find out the role of Domestic Investment (PMDN) and Foreign Investment (PMA) to reduce poverty in Indonesia. This study uses quantitative methods by processing data on the number of PMDN and PMA and the magnitude of poverty rates issued by the Central Bureau of Statistics, Bank Indonesia and the Ministry of Manpower and Transmigration. The analysis uses the method of panel least square dummy variables by conducting a combination analysis of time series data and cross section data by taking samples in 33 provinces in Indonesia. The amount of data used is a ten-year span, i.e., from 2010 to 2019. The results of the study prove that when there is an increase in domestic investment in thirty provinces in Indonesia, the poverty rate in Indonesia will decrease. The same result also occurred that foreign investment has a significant effect on the poverty rate in Indonesia. Although in general PMDN and PMA have a positive and significant effect in helping accelerate the reduction of poverty in Indonesia, based on the results of the analysis there are one to two provinces where PMDN or PMA do not have a positive effect and significant to reduce poverty in the province. Based on the results of this analysis, it is expected that the government can continue to encourage and create rules and policies that help increase the amount of investment through PMDN and PMA in all provinces, especially provinces that have a positive impact with the PMDN and PMA to improve people's welfare while reducing poverty in all provinces in Indonesia.